Integrated quantum photonics - Aungskunsiri, K; Bonneau, D; Carolan, J; Engin, E; Fry, D; Hadden, J; Kalasuwan, P; Kennard, J; Knauer, S; Lawson, T; Marseglia, L; Martin-Lopez, E; et al. (2012)
We describe our developments in integrated quantum photonics, including waveguide circuits to implement quantum logic operations, quantum metrology and quantum walks. ©2010 IEEE.